Odpowiedź :
Odpowiedź:
27, 29, 31, 33
Wyjaśnienie:
(2x + 1) + (2x + 3) + (2x + 5) + (2x + 7) = 8x + 16 = 8*(x + 2)
8*(x + 2) = 15*y
y = 8
x + 2 = 15
x = 13
2*13+ 1 = 27
2*13+ 3 = 29
2*13+ 5 = 31
2*13+ 7 = 33
Nie jestem pewien, że jest dobrze, ale mam nadzieję, że chociaż trochę pomogłem.
Pozdrawiam, Julek :)
Odpowiedź:
Odp. 27,29,31,33
Szczegółowe wyjaśnienie:
(2n + 1) + (2n + 3) + (2n + 5) + (2n + 7 ) = 8n + 16 = 8*(n + 2)
zatem
8*( n + 2) = 15 *k
Niech k = 8
wtedy n + 2 = 15
n = 13
========
Mamy
2*13 + 1 = 27
2*13 + 3 = 29
2*13 + 5 = 31
2*13 + 7 = 33
spr> 27 + 29 + 31 + 33 = 120 = 8*15
Odp. 27,29,31,33